2023
DOI: 10.3390/cancers15102860
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-Lipid Nanoparticle (LNP) Delivery of Humanized EpCAM-CD3 Bispecific Antibody Significantly Blocks Colorectal Cancer Tumor Growth

Abstract: The epithelial cell adhesion molecule (EpCAM) is often overexpressed in many types of tumors, including colorectal cancer. We sequenced and humanized an EpCAM mouse antibody and used it to develop bispecific EpCAM-CD3 antibodies. Three different designs were used to generate bispecific antibodies such as EpCAM-CD3 CrossMab knob-in-hole, EpCAM ScFv-CD3 ScFv (BITE), and EpCAM ScFv-CD3 ScFv-human Fc designs. These antibody designs showed strong and specific binding to the EpCAM-positive Lovo cell line and T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In the field of tumor therapy, the application of LNP-assisted mRNA vaccines has aroused extensive research interest [ 154 ]. In past studies [ 155 , 156 , 157 , 158 , 159 , 160 ], researchers have achieved a series of encouraging results by using LNP carriers to deliver mRNA vaccines to tumor models (such as liver cancer). Some studies [ 161 , 162 , 163 , 164 ] have shown that LNP carriers can effectively deliver mRNA vaccines and stimulate tumor antigen-specific immune responses in liver tumor mouse models.…”
Section: Application Of Lnp-assisted Mrna Vaccines In Tumor Immunothe...mentioning
confidence: 99%
“…In the field of tumor therapy, the application of LNP-assisted mRNA vaccines has aroused extensive research interest [ 154 ]. In past studies [ 155 , 156 , 157 , 158 , 159 , 160 ], researchers have achieved a series of encouraging results by using LNP carriers to deliver mRNA vaccines to tumor models (such as liver cancer). Some studies [ 161 , 162 , 163 , 164 ] have shown that LNP carriers can effectively deliver mRNA vaccines and stimulate tumor antigen-specific immune responses in liver tumor mouse models.…”
Section: Application Of Lnp-assisted Mrna Vaccines In Tumor Immunothe...mentioning
confidence: 99%
“…Catumaxomab is a similar BiTE antibody construct targeting EpCAM and CD3 that was initially approved in the European Union in 2009 for intraperitoneal treatment of malignant ascites but was withdrawn for commercial reasons in 2017 [101]. Interestingly, a recent paper on mRNA-lipid nanoparticle (LNP) delivery of EpCAM-CD3 BiTEs shows promise in vivo [102]. Intratumoral injection of EpCAM-CD3 hFc mRNA-LNPs (1 µg/mouse) in combination with intravenous injection of T cells significantly decreased OVCAR-5 tumor growth in mice [102].…”
Section: Antibodiesmentioning
confidence: 99%
“…Interestingly, a recent paper on mRNA-lipid nanoparticle (LNP) delivery of EpCAM-CD3 BiTEs shows promise in vivo [102]. Intratumoral injection of EpCAM-CD3 hFc mRNA-LNPs (1 µg/mouse) in combination with intravenous injection of T cells significantly decreased OVCAR-5 tumor growth in mice [102].…”
Section: Antibodiesmentioning
confidence: 99%
“…When used with mRNA-LNP technology, these antibodies showed high specificity for killing EpCAM + T cells. The EpCAM scFv-CD3 scFv-human Fc also significantly blocked OVCAR-5 xenograft tumor growth in vivo [ 69 ]. The applications of in vivo therapeutic antibody expression as treatments for specific diseases are summarized in Fig.…”
Section: Applications Of Mrna Vaccines and Drugsmentioning
confidence: 99%